Model reconstruction for 3d vizualization of cultural heritage sites using open data from social media: the case study of Soli, Cyprus - Themistocleous, Kyriacos (My University, 2017)
Given recent military conflicts, terrorism and natural disasters, many cultural heritage sites are increasingly being destroyed. As well, several of these sites are difficult to monitor due to their inaccessibility and remoteness. As aerial surveillance using drones and/or low altitude systems is more common, there is a vast amount of open data now available on social media, which are posted every day on the internet. Many of the videos posted do not include any information on the equipment that was used to acquire the video. Such media can be used to create 3D models and ortho-images of cultural heritage sites in order to monitor and document their existing status. Using open data that is available on the internet, this study used a range of imaging technique to estimate 3D landscape features from 2D image sequences subtracted from video, as well as applied image distortion correction and geo-referencing. The 3D models can be viewed using Google Earth and also be used to create ortho-image, drawings, and digital surface modeling for cultural heritage and archaeological purposes in remote or inaccessible areas. Such 3D models can be used to monitor and geo-reference cultural heritage sites. Social media can be used as a new source of information by archaeologists and cultural heritage experts to monitor and document cultural heritage sites that are in inaccessible areas, due to conflict, terrain or natural disasters.
Keywords: 3D model; Archaeology; Cultural heritage; Open source data; Photogrammetry; Remote sensing